“The Impact of the Metaverse on Purchasing Decisions and Consumer Behavior among The SHEIN Platform User Experience as a Case Study’’ (Journal of Human Sciences, 2026)
This study explores the impact of the Metaverse on purchasing decisions and consumer behavior among students, using the SHEIN platform as a case study. The research employed a descriptive-analytical approach, collecting data through an electronic questionnaire distributed to 170 students. The study focused on three main dimensions: interaction in the Metaverse, digital advertisements, and user experience. Results indicated that interaction within the Metaverse enhances shopping experiences and positively influences purchasing decisions, particularly through social feedback and reviews. Personalized ads and immersive promotional experiences were found to increase purchase intentions. Regarding user experience, ease of use and visually appealing virtual store designs were critical for consumer satisfaction. The study revealed no statistically significant differences based on gender or age, suggesting uniform digital consumer behavior among university students. These findings provide valuable insights for developing effective marketing strategies in the Metaverse, emphasizing the importance of interaction and user experience to foster brand loyalty. The research contributes to understanding the evolving dynamics of digital consumer behavior in virtual environments.